Inflammatory Immune Responses in Patients with Tick-Borne Encephalitis: Dynamics and Association with the Outcome of the Disease - Petra Bogovič; Lara Lusa; Miša Korva; Stanka Lotrič-Furlan; Katarina Resman-Rus; Miša Pavletič; Tatjana Avšič-Županc; Klemen Strle; Franc Strle (Microorganisms, 2019)
Information on the association of inflammatory immune responses and disease outcome after tick-borne encephalitis (TBE) is limited. In the present study, we assessed the levels of 24 cytokines/chemokines associated with innate and adaptive immune responses in matched serum and cerebrospinal fluid (CSF) samples of 81 patients at first visit, and in serum at follow-up time points. Serum levels of several cytokines/chemokines obtained during the meningoencephalitic phase of TBE differed compared to the levels at a follow-up visit 2 months later; several significant differences were also found in cytokine/chemokine levels in serum at 2 months compared to the last time point, 2−7 years after acute illness. Cytokines/chemokines levels in CSF or serum obtained at the time of acute illness or serum levels obtained 2 months after the onset of TBE did not have predictive value for an unfavorable outcome 2−7 years later. In contrast, serum levels of mediators associated with Th17 responses were lower in patients with unfavorable outcome whereas those associated with other adaptive or innate immune responses were higher at the last visit in those with an unfavorable outcome. These findings provide new insights into the immunopathogenesis of TBE and implicate inflammatory immune responses with post-encephalitic syndrome years after the initial infection.